A study of factors for private label brands' success in food, grocery and apparels. (2016) - Singh, Ajay; De, Debdeep
The purpose of this paper is to identify the factors considered by consumers while deciding for a private label brand and ascertain how an organisation increases the sales of its private labels. The study conducted is exploratory in nature. A structured questionnaire was developed to collect data from various retail consumers of the National Capital Region in India, and subsequent factor analysis was performed. The outcome of the study reflects that price consciousness, quality variability, brand image, self-perception and store image are the factors based on which a consumer makes a purchase decision for a private label brand. These factors may change to some extent owing to a completely different value proposition provided by the private labels as compared to national brands. To boost the sales of private labels and enhance their image in the minds of the consumers, it is important for an organisation to focus on few key factors as identified in the findings. This study would reveal a valuable perspective for an emerging private label market in India.